Comparing paleo-oxygenation proxies (benthic foraminiferal surface porosity, I/Ca, authigenic uranium) on modern sediments and the glacial Arabian Sea - Lu, Wanyi; Wang, Yi; Oppo, Delia W; Nielsen, Sune G; Costa, Kassandra M (PANGAEA, 2022)
A total of 70 core-top samples and 24 down-core samples were used in this study. All sediment samples were taken from Woods Hole Oceanographic Institution (WHOI) Seafloor Samples Repository. For the core-top calibrations, samples were taken from the top 5 cm of most cores. Cores TN041-8PG and 8JPC are from the center of the modern Arabian Sea Oxygen Minimum Zone. Core 8PG was sampled every 16 cm from top to bottom (a total of 224 cm, extending to ~ 15.6 kyr BP). We extended the record of 8PG to ~30 kyr BP using 8JPC, which was also sampled at 16 cm intervals. All samples were freeze-dried and then aliquoted for bulk sediment geochemistry analyses. The rest of sediments were wet-sieved to > 63 µm fraction with de-ionized water, and oven-dried at 45°C. Benthic foraminifera Cibicidoides spp., Planulina sp., and Globobulimina affinis were picked from the > 212 µm fraction. Photos of benthic foraminifera were taken using a Scanning Electron Microscope (SEM) (Hitachi model TM3000) at WHOI. Benthic surface porosity was determined from the SEM photos. Benthic foraminifera I/Ca analyses and bulk sediment geochemistry were performed on a Thermo Scientific iCAP Qc ICP-MS at WHOI.
Keywords: Arabian Sea; authigenic uranium; Benthic foraminifera; benthic surface porosity; Bottom-water oxygen; iodine/calcium